Severe acute colitis related to levodopa treatment - ZANELLI, M.; ZANETTI, E.; BISAGNI, A.; DI FABIO, S.; CREMASCHI, F.; MONTANARI, P.; MENGOLI, M.C.; DE MARCO, L. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
The first case of severe drug-induced gastrointestinal injury related to levodopa is described. The 86-year-old patient experienced acute colitis temporally related to the intake of the drug with complete resolution of symptoms on levodopa withdrawal. Awareness of the possibility of a levodopa-related damage on colon biopsies performed for acute colitis is of paramount importance for pathologists. However, in order to exclude or confirm a drug-related damage an effective communications between clinicians and pathologists is always required.